2016
DOI: 10.1007/s10493-016-0013-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the prevalence and infestation levels of Varroa destructor in honeybee colonies in two highland agro-ecological zones of Uganda

Abstract: Varroa mites are ecto-parasites of honeybees and are a threat to the beekeeping industry. We identified the haplotype of Varroa mites and evaluated potential factors that influence their prevalence and infestation levels in the eastern and western highland agro-ecological zones of Uganda. This was done by collecting samples of adult worker bees between December 2014 and September 2015 in two sampling moments. Samples of bees were screened for Varroa using the ethanol wash method and the mites were identified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 37 publications
5
29
2
Order By: Relevance
“…Thus, a correlation with latitude might be due to some specific coincidences. In this study, no correlation was found between the Varroa levels in hives and the altitude of the sampling site, in accordance with other data from tropical climates (Chemurot et al 2016;Mortensen et al 2016).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Thus, a correlation with latitude might be due to some specific coincidences. In this study, no correlation was found between the Varroa levels in hives and the altitude of the sampling site, in accordance with other data from tropical climates (Chemurot et al 2016;Mortensen et al 2016).…”
Section: Discussionsupporting
confidence: 91%
“…These observations might also reflect the lower preference of the mites for worker cells in this honey bee species, explaining the fewer double or triple infestations found. This would also explain the low numbers of mites found on adult bees, and the relatively low levels observed in their brood in terms of prevalence and infection rates, similar to those reported in other east African countries (Muli et al 2014;Chemurot et al 2016;Mortensen et al 2016).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The Varroa mite is considered to be cosmopolitan (Wilfert et al 2016), and infestation level on honey bees around the world varies from 2.0 to 31.4% (Akyol et al 2006;Akyol & Yeninar 2009;Mumbi et al 2014;Muli et al 2014;Chemurot et al 2016;Giaco-bino et al 2016;Gracia et al 2017). The infestation levels of this mite are higher in A. mellifera colonies from temperate climates than colonies from subtropical climates (Giacobino et al 2016), suggesting that climate can have an important role in the host-parasite interaction (Muli et al 2014) and may influence the mite infestation rates, but the influence of climate parameters on this mite are unclear (Rosenkranz et al 2010).…”
Section: Introductionmentioning
confidence: 99%